The philosophy of Arab Islamic education and its impact on education - Hassan, Rafa AbdulLatif (Al-Adab Journal, 2021)
Islam has a special method in education, which is a comprehensive treatment of the human soul with the innate nature created by God Almighty with infinite precision and not oblivious to anything. When an individual thinks about the means of education based on the Islamic approach, he marvels at the infinite precision with which a person treats, starting from treating his small parts and ending with it as a whole and as one unit, the individual is able to start and has taken his share of Islamic behavioral nutrition in refining and controlling its psychological aspects.